Shifting power asymmetries in scientific teams reveal China’s rising leadership in global science - Renli Wu; Christopher Esposito; James Evans (Proceedings of the National Academy of Sciences, 2025)
China’s emergence as one of the world’s top producers of high-quality science raises critical questions about its trajectory toward achieving scientific leadership. Traditional methods for evaluating the power of national scientific ecosystems, however, often overlook the nuances of a country’s global influence. In this perspective, we introduce a framework that highlights shifting power dynamics in international scientific collaborations, focusing on whether leadership positions in international scientific teams are moving from one country to another. Using rich sociological data from nearly 6 million scientific publications, we document a marked shift in team leadership from Western countries to China. In particular, the share of team leaders involved in U.S-China scientific collaborations that were affiliated with Chinese institutions grew from 30% of the total in 2010 to 45% in 2023. We further explore the implications of China’s rise by forecasting when Chinese scientists are projected to achieve parity in leadership vis-à-vis the United States, including in 11 critical technology areas that are focal points of technological development, and by analyzing how a potential decoupling of U.S.-Chinese science might affect Chinese scientific leadership. We conclude by considering the impacts of China’s growing investments in the training of young scientists in countries participating in the Belt and Road Initiative.